Theoretical Analysis for Stability Evaluation of Rock Mass Engineering Structure under Combined Compression-Shear Loading: A Case Study of Inclined Pillar - Lijun Sun; Yicheng Ye; Binyu Luo; Nanyan Hu; Pengcheng Li (Applied Sciences, 2021)
An inclined pillar is a typical support structure under compression and shear loads for underground mining. The shear load caused by the inclination of the ore-body affects the bearing capacity of the pillar. At present, there is no systematic investigation on the influence of shear load on the stress state evolution and bearing capacity of the inclined pillar. Additionally, there is still a lack of effective evaluation of the bearing capacity of the inclined pillar in the presence of additional shear load. In this research, the theoretical analysis method is used to solve these problems. First, the compressive and shear load components on the inclined pillar were calculated by the tributary area method, and the average stress state of the inclined pillar, considering the influence of the shear load, was characterized by a series of generalized stress circles. The factors that affect the shear load, such as the area extraction ratio, the inclination of the ore-body, and the in-situ stress ratio, were analyzed, and it reveals that there are three kinds of stress paths of the inclined pillar and their trajectories are straight line, circle, and curve, respectively. Then, a shear strength model was proposed to evaluate the bearing capacity of inclined pillars. The expression of this model is multiplied by a vertical pillar strength model and a dimensionless coefficient that is named the contribution factor of shear load (CFSL). Some cases of inclined pillars were employed to verify the rationality of this model. Finally, the factors that affect the bearing capacity of pillars were analyzed. This investigation presents that the shear load affects the stress path and determines the bearing capacity of the pillar. Therefore, the shear load should not be neglected in pillar design and stability analysis.